2009
DOI: 10.1097/pcc.0b013e3181c515ca
|View full text |Cite
|
Sign up to set email alerts
|

Single-institution experience with inter-hospital extracorporeal membrane oxygenation transport: A descriptive study*

Abstract: Outcomes of patients transported by an experienced extracorporeal membrane oxygenation team to a busy extracorporeal membrane oxygenation center are very comparable to outcomes of nontransported extracorporeal membrane oxygenation patients as reported in the Extracorporeal Life Support Organization registry. As has been previously reported, interhospital extracorporeal membrane oxygenation transport is feasible and can be accomplished safely. Other experienced extracorporeal membrane oxygenation centers may wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 9 publications
1
57
0
1
Order By: Relevance
“…Data from the USA of interhospital extracorporeal membrane oxygenation transport revealed that transport was carried out by airborne ambulance in 87.5% of cases. 8 In Japan, the Fire Defense Act amended in 1963 assigned ambulance service responsibilities to Fire Defense organizations, providing a wellestablished ground ambulance system covering the entire nation. 9,10 On the other hand, the airborne ambulance system has only recently started operating, being also known as "Doctor Helicopters".…”
Section: Discussionmentioning
confidence: 99%
“…Data from the USA of interhospital extracorporeal membrane oxygenation transport revealed that transport was carried out by airborne ambulance in 87.5% of cases. 8 In Japan, the Fire Defense Act amended in 1963 assigned ambulance service responsibilities to Fire Defense organizations, providing a wellestablished ground ambulance system covering the entire nation. 9,10 On the other hand, the airborne ambulance system has only recently started operating, being also known as "Doctor Helicopters".…”
Section: Discussionmentioning
confidence: 99%
“…Mobile ECMO units expanded ECMO application to critically ill patients in remote institutions for salvage, stabilization and interhospital transfer (1-5850 km) [25,26,29,69,70]. …”
Section: Recent Findingsmentioning
confidence: 99%
“…ECMO is a first-line device that 'covers' biventricular and lung function, fits almost all patients and clinical scenarios, offers variability of cannulation (central, peripheral), is rapidly deployable, versatile, familiar, and economical [4 ,12,33,52,57]. Although improved ECMO technology has contributed to improved 'time and team-dependent' results[10,12,14,25,26,29,44,52,66,67,69], according to larger-scale data[4 ,5,13,15,16,60,64,65,102] and expert opinion the 'overall survival remains persistently poor after ECMO support, despite maintaining systemic blood flow and oxygenation. Until we understand how to prevent vital organ injury, this will not change'[109].ECMO disadvantages include blood trauma inside the oxygenator, systemic inflammatory response triggering, increased anticoagulation, inadequate left heart unloading in severe left-ventricular failure, shorter support duration, decreased mobilization, potential for extubation and oral feeding[4 ,5,12,14-16,40].…”
mentioning
confidence: 99%
“…Seymour et al published a retrospective cohort study of 191 patients on mechanical ventilation, transferred by helicopter during 36 months. 32 They recorded only minor events 42 Observational, 23 One intensivist physician, Ambulance, airplane, No deaths or major complications due to retrospective one heart surgeon, one ICU nurse, militar airplane transports (not dedicated team) Haneya et al 43 Observational, 38 One intensivist physician, Ambulance, helicopter During transports for distances greater than retrospective one perfusionist, one nurse, 350 km a stop was needed because the one heart surgeon, oxygen supply was insufficient; a case of replacement of an oxygenator due to partial clogging of the membrane Clement et al 44 Descriptive, 112 One ECMO coordinator, one Helicopter, No deaths during transports; retrospective pediatric heart surgeon, airplane, ambulance one assistant surgeon, one intensivist physician no detailed information about adverse events during transfers Ciapetti et al 45 Descriptive 12 ARDS cases, One intensivist physician, Ambulance, airplane, All transfers performed successfully; observational, among which one heart surgeon, one helicopter absence of noteworthy incidents 4 transported cardiologist, one perfusionist, with ECMO one nurse Lucchini et al 46 Observational, 42 ARDS cases, Two intensivist physician, Ambulance, airplane All transfers performed successfully; retrospective which 29 one perfusionist, one nurse absence of noteworthy incidents with ECMO MICU, mobile intensive care unit; ECMO, extracorporeal membrane oxygenation; ECLS, extracorporeal life support; ICU, intensive care unit; ARDS, acute respiratory distress syndrome (22% of cases), showing that this mode of transport can be performed safely. 32 Also the secondary transfers of 173 patients with intraaortic balloon pump by plane, helicopter or mobile intensive care unit were substantially free from relevant clinical and mechanical complications.…”
Section: Inter-hospital Transport Complicationsmentioning
confidence: 99%